IMPACT OF COVID-19 ON THE SERVICE INDUSTRY: A REVIEW - Bashirun, Siti Norashikin; Mohd Taufik, Mohamad Qandias; Mohamad Razlan, Mohamad Shahrul Isa; Azrien Azry, Nur Allyssa Azry; Abdul Razak, Nurin Liyana Wadiyah; Alamein, Ameishah Khairiah (Jurnal 'Ulwan, 2022)
The global economy is being impacted by coronavirus disease (COVID-19) in a way that has never been seen before. Many businesses are affected which resulted in significant changes in the service industry. This paper aims to present reviews of the literature on the impact of COVID-19 on the service industry, with a focus on tourism, healthcare, IT, and communication and education. The review showed that the impact extended beyond business performance to other areas, such as mental health and well-being. This review will provide a comprehensive understanding of COVID-19's effects on the service sector, as well as those of its alternatives and potential future practices.